Promoting sustainability development through agrotourism activities in Ranau, Sabah - Juliana Langgat; Kamarul Mizal Marzuki; Roslinah Mahmud; Khairul Hanim Pazim; Noor Fzlinda Fabeil; Marry Tracy Pawan (Penerbit Universiti Malaysia Sabah, 2024)
Promoting sustainability through agrotourism is an excellent approach. Farmers could promote sustainability and provide opportunities for visitors to experience farming in addition to their own agricultural endeavors. One of the areas in Sabah that attracts most visitors is Ranau, which is recognized as a tourist destination and core for the agricultural sector. The study’s primary goal was to use agrotourism to promote sustainable development. Five farmers were randomly chosen for this study and conducted in-depth interviews to gather data using a qualitative methodology. Three stages of the coding method in qualitative data analysis were used to analyze the study’s results and produce fresh research findings. The results of the study indicated that agrotourism activities were a possible way to promote sustainability. Activities related to agrotourism have the potential to protect the environment, boost economic viability, engage communities and raise awareness and education. The local council and state government can make extensive use of these findings and prepare guidelines and policies. This would help the agrotourism sector, particularly in the Ranau district, which is a popular tourist destination in Sabah. It might also serve as a pilot study that other districts hope to promote their area as an agrotourism destination could utilize as a point of reference..